Emergency ethics - Viens, A. M. (Adrian M.); Selgelid, Michael J. (Farnham, Surrey, England : Ashgate, 2012)
Emergencies are extreme events which threaten to cause massive disruption to society and negatively affect the physical and psychological well-being of its members. They raise important practical and theoretical questions about how we should treat each other in times of'crisis'. The articles selected for this volume focus on the nature and significance of emergencies; ethical issues in emergency public policy and law; war, terrorism and supreme emergencies; and public health and humanitarian emergencies. Together they demonstrate the normative implications of emergencies and provide multi-disciplinary perspectives on the ethics of emergency response.
Includes bibliographical references and index.
Keywords: Emergencies -- Philosophy; Emergency management -- Moral and ethical aspects